Legal Framework of the Digital Services Act for Online Platforms - Elif Beyza Akkanat Öztürk; Eylül Erva Akın (İdare Hukuku ve İlimleri Dergisi)
This paper comprehensively evaluates the legal obligations prescribed for online platforms under the Digital Services Act (DSA). It examines the current impacts of DSA on online platforms and potential future implications. The DSA represents one of the European Union’s most comprehensive and innovative initiatives to regulate digital spaces. The objective of this regulatory framework is to clarify the responsibilities and obligations of online platforms and to provide secure and transparent digital services. In other words, the DSA aims to reduce legal uncertainties in the internet environment, protect user rights and control the impact of platforms on society. In this perspective, the regulation of online platforms and the existing legal framework for digital services within the European Union are analysed. The evolving role of online platforms with DSA and the responsibilities of this new role are discussed.This study examines content moderation and the liability regime under the DSA, highlighting the balance between fundamental rights and freedoms and the importance of transparency obligation. Special attention is given to the protection of children online, assessing the adequacy of the DSA in safeguarding children’s rights, the scope of platform obligations and how the concept of harmful content is addressed. Finally, terms of use involving content moderation and protection of special categories of personal data and behavioural advertising practises are examined. The impact of DSA on the operation of online platforms and user rights is evaluated within the framework of transparency and accountability principles.